Evaluation of photovoltaic properties of nanocrystalline-FeSi2/Si heterojunctions. (September 2016) - Shaban, Mahmoud; Bayoumi, Amr M.; Farouk, Doaa; Saleh, Mohamed B.; Yoshitake, Tsuyoshi
Highlights: Nanocrystalline-FeSi2 /Si heterojunctions were fabricated and experimentally tested. Uses experimentally-extracted parameters of NC-FeSi2 . A heterojunction structure using nanocrstalline-FeSi2 and nanocrystalline-Si is proposed. Photovoltaic properties of the proposed device were numerically evaluated. A conversion efficiency of 25% can be achieved for devices with defect density, below 10 14 cm −3 eV −1 in NC-FeSi2 layer. Abstract: In this paper, an application of nanocrystalline iron disilicide (NC-FeSi2 ) combined with nanocrystalline-Si (NC-Si) in a heterostructured solar cell is introduced and numerically evaluated in detail. The proposed cell structure is studied based on an experimental investigation of photovoltaic properties of NC-FeSi2 /crystalline-Si heterojunctions, composed of unintentionally-doped NC-FeSi2 thin film grown on Si substrate. Photoresponse measurement of NC-FeSi2 /crystalline-Si heterojunction confirmed ability of NC-FeSi2 to absorb NIR light and to generate photocarriers. However, collection of these carriers was not so efficient and a radical improvement in design of the device is required. Therefore, a modified device structure, comprising of NC-FeSi2 layer sandwiched between two heavily-doped p - and n -type NC-Si, is suggested and numerically evaluated. Simulation results showed that the proposed structure would exhibit a relatively high conversion efficiency of 25%, due to an improvement in collection efficiency of photogenerated carriers in the NC-FeSi2 and NC-Si layers. To attain such efficiency, defect densities in NC-FeSi2 and NC-Si layers should be kept less than 10 14 and 10 16 cm −3 eV −1, respectively. Remarkable optical and electrical properties of NC-FeSi2, employed in the proposed structure, facilitate improving device quantum efficiency spectrum providing significant spectrum extension into the near-infrared region beyond Si bandgap.